A Straightforward Approach to the Synthesis of Disubstituted Cyclopentenones. Issue 11 (4th March 2020) - Roldão, Mariane V.; Souza‐Filho, Luis Gustavo; Almeida, Wanda P.; Coelho, Fernando
Abstract : In this paper we describe an approach for the synthesis of a set of new diversely di‐substituted cyclopentenones using Morita–Baylis–Hillman (MBH) adducts as building blocks. The synthesis was performed with few steps, but the overall yield reached 34 %. A key step of this approach is a rhodium mediated 1, 4‐addition reaction on adequately functionalised MBH adducts, which leads to the creation of cinnamate ester derivatives with high E selectivity. These intermediates were used as substrates for an intramolecular Friedel‐Crafts cyclisation reaction to achieve the required 2, 3‐substituted cyclopentenones. As far as we know, this is the first report to describe the synthesis of substituted cyclopentenones that directly employ MBH adducts as building blocks. Abstract : We describe an approach to prepare di‐substituted cyclopentenones with potential anti‐inflammatory activity, using MBH adducts as building blocks. The synthesis is based on a rhodium mediated 1, 4‐addition and an intramolecular Friedel‐Crafts type reaction.